'It's really good…why hasn't it happened earlier?' Professionals' perspectives on the benefits of communication assistance in the New Zealand youth justice system. Issue 2 (June 2020) - Howard, Kelly; McCann, Clare; Dudley, Margaret
Communication assistance is a form of specialist support for witnesses and defendants in justice settings who have been identified as having communication difficulties. This new role in New Zealand is modelled on the role of the intermediary in England and Wales. To date however, there has been no published review or evaluation on how communication assistance is functioning and being viewed by professionals in practice. This study provides a qualitative analysis of professionals' perspectives (n = 28 participants) on the benefits of communication assistance for young people facing criminal charges in the New Zealand youth justice system. The main finding is that professionals are overwhelmingly in support of this new role. Professionals considered that communication assistance helps put the young person at the centre of youth justice, brings new knowledge and a fresh perspective, and helps the system to function as it ideally should.